Biological evaluation of chitosan‐based in situ‐forming hydrogel with low phase transition temperature. Issue 10 (25th October 2014) - Dang, Qi Feng; Yan, Jing Quan; Lin, Hong; Liu, Cheng Sheng; Chen, Xi Guang; Ji, Qiu Xia; Li, Jing; Liu, Ya
ABSTRACT The aims of current study were to choose a method for preparing sterile chitosan‐α, β‐glycerophosphate (CS‐α, β‐GP) in situ‐forming hydrogel which had potential applications in tissue engineering and evaluated its biocompatibility and degradation characteristics. The results of sterilization stability tests indicated that sterile formulations could be obtained by ultraviolet irradiation of CS powders, 0.22 µm filtration of α, β‐GP and lactic acid solutions, and sterile preparation of CS‐α, β‐GP formulations. The obtained sterile CS‐α, β‐GP formulations showed low hemolysis rates and low BSA adsorption at physiological conditions. When injected in vivo the CS‐α, β‐GP sol turned into gel implant in situ and could be degraded gradually. A minimal inflammatory reaction which could not be found by macroscopic evaluation was induced after injection and new capillary formation was found around the hydrogel humps, making the CS‐α, β‐GP hydrogel worthwhile to be considered for tissue engineering and biomedical applications. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41594.